Impact of Obesity on Outcomes in Breast Reconstruction: A Systematic Review and Meta-Analysis - Panayi, Adriana C.; Agha, Riaz A.; Sieber, Brady A.; Orgill, Dennis P. (Journal of Reconstructive Microsurgery, 2018)
Background Increased rates of both breast cancer and obesity have resulted in more obese women seeking breast reconstruction. Studies demonstrate that these women are at increased risk for perioperative complications. A systematic review was conducted to assess the outcomes in obese women who underwent breast reconstruction following mastectomy.Methods Cochrane, PUBMED, and EMBASE electronic databases were screened and data were extracted from included studies. The clinical outcomes assessed were surgical complications, medical complications, length of postoperative hospital stay, reoperation rate, and patient satisfaction.Results Out of 33 studies met the inclusion criteria for the review and 29 provided enough data to be included in the meta-analysis (71,368 patients, 20,061 of whom were obese). Obese women (body mass index > 30 kg/m2) were 2.29 times more likely to experience surgical complications (95% confidence interval (CI) 2.19–2.39; p < 0.00001), 2.89 times more likely to have medical complications (95% CI 2.50–3.35; p < 0.00001), and had a 1.91 times higher risk of reoperation (95% CI 1.75–2.07; p < 0.00001). The most common complication, wound dehiscence, was 2.51 times more likely in obese women (95% CI 1.80–3.52; p < 0.00001). Sensitivity analysis confirmed that obese women were more likely to experience surgical complications (risk ratio 2.36, 95% CI 2.22–2.52; p < 0.00001).Conclusions This study provides evidence that obesity increases the risk of complications in both implant-based and autologous reconstruction. Additional prospective and observational studies are needed to determine if the weight reduction prior to reconstruction reduces the perioperative risks associated with obesity.
Keywords: plastic surgery; breast reconstruction; obesity; breast surgery complication; breast cancer